2006
DOI: 10.1038/sj.mp.4001910
|View full text |Cite
|
Sign up to set email alerts
|

Violent behavior associated with hypocholesterolemia due to a novel APOB gene mutation

Abstract: A 26-year-old male, the index patient, presented with persecutory delusions and suicidal behavior. He had 10 paternal male relatives in two prior generations. Five of them died by violent suicide and one, of the five, also committed a double homicide. The index patient was found to be hypocholesterolemic due to being heterozygous for a novel mutation of apolipoprotein B (apoB-29.4). His mother and paternal grandmother were normocholesterolemic, whereas a surviving paternal uncle was hypocholesterolemic and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
(43 reference statements)
1
10
0
1
Order By: Relevance
“…This leads to damage to the dorsal root ganglia, spinocerebellar tracts, retina, and cerebellum similar to those observed in vitamin E deficient mammals. Vitamin E is essential for neurological function and is transported in plasma in association with the apoB-containing lipoproteins [21]. The retinal degeneration, again peculiar to ABL, is thought to be caused by combined deficiency of vitamins A and E [22].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to damage to the dorsal root ganglia, spinocerebellar tracts, retina, and cerebellum similar to those observed in vitamin E deficient mammals. Vitamin E is essential for neurological function and is transported in plasma in association with the apoB-containing lipoproteins [21]. The retinal degeneration, again peculiar to ABL, is thought to be caused by combined deficiency of vitamins A and E [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the price to pay for such a protection from CHD may be an increased risk of violence. In a family with FHBL, Edgar et al (2007) found a significant association between hypocholesterolemia and violent behavior. The odds ratio for the association was 16.9 (95% confidence interval 1.1-239.3).…”
Section: Aggressionmentioning
confidence: 99%
“…Upon examination, it was discovered that 5 out of 10 males of his relatives had committed violent suicide and one a double homicide. The father of the index patient and the paternal grandfather were both heterozygotic for the novel mutation and both displayed hypocholesterolemia, further supporting a heritable association between cholesterol metabolism, low cholesterol, and possible violent behavior and violent suicide (Edgar et al, 2007).…”
Section: Cholesterol and Violencementioning
confidence: 73%